C-type lectin B (SpCTL-B) regulates the expression of antimicrobial peptides and promotes phagocytosis in mud crab Scylla paramamosain. (July 2018) - Wei, Xiaoyuan; Wang, Limin; Sun, Wanwei; Zhang, Ming; Ma, Hongyu; Zhang, Yueling; Zhang, Xinxu; Li, Shengkang
Abstract: As pattern recognition receptors, C-type lectins (CTLs) play important roles in immune system of crustaceans through identifying and binding to the conservative pathogen-associated molecular patterns (PAMPs) on pathogen surfaces. In this study, a new CTL, Sp CTL-B, was identified from the hemocytes of mud crab Scylla paramamosain . The full-length of Sp CTL-B cDNA was 1278 bp with an open reading frame (ORF) of 348 bp. The predicted Sp CTL-B protein contains a single carbohydrate-recognition domain (CRD). Sp CTL-B transcripts were distributed in all examined tissues with the highest levels in hepatopancreas. After challenged with Vibrio parahaemolyticus, LPS, polyI:C and white spot syndrome virus (WSSV), the mRNA levels of Sp CTL-B in hemocytes and hepatopancreas were up-regulated. The recombinant Sp CTL-B (r Sp CTL-B) purified by Ni-affinity chromatography showed stronger binding activities with Staphylococcus aureus, β- hemolytic Streptococcus, Escherichia coli, Aeromonas hydrophila, Vibrio alginolyticus than those with V. parahaemolyticus and Saccharomyces cerevisiae . r Sp CTL-B exhibited a broad spectrum of microorganism-agglutination activities against Gram-positive bacteria ( S. aureus, β- hemolytic Streptococcus ) and Gram-negative bacteria ( E. coli, V. parahaemolyticus, A. hydrophila, V. alginolyticus ) in a Ca 2+ -dependent manner. The agglutination activities of r Sp CTL-B could be inhibited by D-mannose and LPS, but not byd -fructose and galactose. The antimicrobial assay showed that r Sp CTL-B exhibited the growth inhibition against all examined gram-positive bacteria and gram-negative bacteria. When Sp CTL-B was silenced by RNAi, the bacterial clearance ability in mud crab was decreased and the transcript levels of five antimicrobial peptides (AMPs) ( Sp Crustin, Sp Histin, Sp ALF4 (anti-lipopolysaccharide factor), Sp ALF5 and Sp ALF6) were significantly decreased in hemocytes. In our study, knockdown of Sp CTL-B could down-regulate the expression of Sp STAT at mRNA transcriptional level and protein translational level in mud crab. Meantime, the phagocytosis rate and the expression of three phagocytosis related genes were declined after RNAi of Sp CTL-B in hemocytes in mud crab. Collectively, our results suggest that Sp CTL-B might play its roles as a pattern recognition receptor (PRR) in immune response towards pathogens infection through influencing the expression of AMPs and the phagocytosis of hemocytes in mud crab S. paramamosain . Highlights: Full-length of Sp CTL-B with 1278 bp was isolated from mud crab. a broad spectrum of agglutination activities in a Ca 2+ -dependent manner. Sp CTL-B regulated AMPs expression and promotes phagocytosis. Sp CTL-B might regulate the expression of AMPs through JAK/STAT pathway.